Methane adsorption and methanol desorption of copper modified boron silicate. Issue 63 (26th October 2018) - Wang, Xueting; Shishkin, Alexander; Hemmingsson, Felix; Skoglundh, Magnus; Martinez-Casado, Francisco Javier; Bock, Lorenz; Idström, Alexander; Nordstierna, Lars; Härelind, Hanna; Carlsson, Per-Anders
Abstract : Boron silicate (BS) with a chabazite framework structure was synthesized and ion-exchanged with copper to form Cu-BS which was capable of oxidizing methane to methoxy species. Abstract : Boron silicate (BS) with a chabazite framework structure was synthesised using a direct route and rigorously characterized before it was ion-exchanged with copper to form Cu-BS. Employing in situ infrared spectroscopy, we show that Cu-BS is capable of oxidising methane to methoxy species and methanol interacts with the boron sites without deprotonation.